Prevalence of cervical pathogens in women with and without inflammatory changes on smear testing. Issue 6886 (1st May 1993) - Parsons, W L; Godwin, M; Robbins, C; Butler, R
Abstract : OBJECTIVE–To assess correlation between nonspecific cervicitis, inflammation, or exudate on cervical smears tests and confirmed presence of known cervical pathogens. DESIGN–Investigation of women attending a family practice clinic for smear test by microbiological screening for Chlamydia trachomatis, Mycoplasma hominis, Ureaplasma urealyticum, Trichomonas vaginalis, Candida species, group B streptococcus, Gardnerella vaginalis, and Neisseria gonorrhoeae. SETTING–Family practice teaching clinic in a university hospital. PATIENTS–411 women presenting for a smear test. MAIN OUTCOME MEASURES–Prevalence of genital infections associated with presence or absence of inflammatory changes on cervical smear. RESULTS–Of the 132 women with inflammatory changes on cervical smear, 64 (48%) had positive cultures. Of the 248 without inflammatory changes, 117 (47%) had positive cultures. Subgroup analysis on individual organisms also showed no significant difference between the two groups. CONCLUSION–Reports of inflammatory changes on cervical smear testing are a poor indicator of infection.